1972
DOI: 10.1017/s0021859600087621
|View full text |Cite
|
Sign up to set email alerts
|

Retention of energy and nitrogen by young sheep on different feeding patterns

Abstract: In each of two experiments the comparative slaughter technique was used to compare the retention of energy by young Border Leicester x Merino wethers when the same total amount of food was offered according to two different feeding regimens. These were designed to simulate, in pens with a diet of pelleted lucerne, feeding patterns typical of continuous and intensive rotational grazing.In the first experiment ten 9-month-old sheep that were offered the same amount of food daily (mean intake 367 g digestible org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1975
1975

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…It must also be remembered that stock movement on R high stocking rate was linked to that on R medium and therefore the ewes and lambs were short of grass for several days before being moved to the next plot. Freer, Jones and Christian (1972) showed that a fluctuating feeding pattern was less efficient than one in which a constant amount of food was offered daily.…”
Section: Net Carcass Outputmentioning
confidence: 99%
“…It must also be remembered that stock movement on R high stocking rate was linked to that on R medium and therefore the ewes and lambs were short of grass for several days before being moved to the next plot. Freer, Jones and Christian (1972) showed that a fluctuating feeding pattern was less efficient than one in which a constant amount of food was offered daily.…”
Section: Net Carcass Outputmentioning
confidence: 99%